Synthesis of ultrafine silicon nitride powders. (1st January 2000) - Orthner, H.R.; Brink, R.; Roth, P.
Silicon nitride powders were synthesised during vapour phase reaction of silicon tetrachloride (SiCl4 ) and ammonia (NH3 ) in a hot wall flow reactor. The effect of process variables on powder composition was investigated by means of thermogravimetric analysis (TGA), specific surface area measurements (BET) and elementary analysis. The powders obtained consist of amorphous silicon nitride (Si3 N4 ) and contain various amounts of volatile ammonium chloride (NH4 Cl). The amount of by-products is strongly dependent on reactor temperature. At high temperatures (T = 1200°C), the amount of volatile compounds is less than 35%, chloride is less than 19% and the specific surface area is around 40m²g -1 . The initial NH3 /SiCl4 ratio used does not significantly affect the ammonium chloride formation, indicating that temperature and flow rate rather than concentration of ammonia determine the formation of NH4 Cl. At temperatures 900°C and lower all chloride originating from SiCl4 was converted to ammonium chloride.